Disease-Modifying Anti-rheumatic Drug Prescription Baihu-Guizhi Decoction Attenuates Rheumatoid Arthritis via Suppressing Toll-Like Receptor 4-mediated NLRP3 Inflammasome Activation - Li, Weijie; Mao, Xia; Wang, Xiaoyue; Liu, Yudong; Wang, Kexin; Li, Congchong; Li, Taixian; Zhang, Yanqiong; Lin, Na (Frontiers in Pharmacology, 2021)
As a traditional Chinese medicine-originated disease-modifying anti-rheumatic drug prescription, Baihu-Guizhi decoction (BHGZD) is extensively used for the treatment of rheumatoid arthritis (RA) with a satisfying therapeutic efficacy. Mechanically, our previous data indicated that BHGZD may ameliorate RA partially by restoring the balance of the “inflammation-immune” system through regulating the TLR4-c-Fos-IL2-TNF-alpha axis. Toll-like receptor 4 (TLR4) has been revealed to be involved in the activation of the NLR family pyrin domain containing 3 (NLRP3) inflammasome complex. Thus, the aim of the current study was to determine the regulatory effects of BHGZD on the TLR4–mediated inflammasome activation during RA progression based on the modified adjuvant-induced arthritis model (AIA-M) and the lipopolysaccharide/adenosine triphosphate (LPS/ATP)–induced pyroptosis cellular models. As a result, oral administration of BHGZD exhibited prominent improvement in the disease severity of AIA-M rats, such as reducing the redness and swelling of joints, arthritis incidence, arthritic scores, and diameter of the limb and increasing pain thresholds. In line with the in vivo findings, BHGZD treatment effectively inhibited the LPS/ATP–induced pyroptosis of both Raw264.7 macrophage and MH7A cells in vitro by reducing pyroptotic cell death morphology (swollen cells) and decreasing propidium iodide–positive and terminal deoxynucleotidyl transferase–mediated dUTP-fluorescein nick end labeling (TUNEL)–positive cells. Notably, the increased expression levels of TLR4, NLRP3, interleukin 1β, and interleukin 18 proteins and the elevated activities of caspase-1 and lactic dehydrogenase in in vivo and in vitro disease models were markedly reversed by the treatment with BHGZD. In conclusion, the above findings proved the immunomodulatory and anti-inflammatory activities of BHGZD, especially in pyroptosis, which may be attributed to the activation of TLR4–mediated NLRP3 inflammasome signaling.